The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1063/1.2422913
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxy of phase pure cubic InN

Abstract: Cubic InN layers were grown by plasma assisted molecular beam epitaxy on 3C-SiC (001) substrates at growth temperatures from 419to490°C. X-ray diffraction investigations show that the layers have zinc blende structure with only a small fraction of wurtzite phase inclusions on the (111) facets of the cubic layer. The full width at half maximum of the c-InN (002) x-ray rocking curve is less than 50arcmin. The lattice constant is 5.01±0.01Å. Low temperature photoluminescence measurements yield a c-InN band gap of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
52
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 19 publications
14
52
1
Order By: Relevance
“…The LDA-BZW results that also agree well with experiment are shown in Table I. In particular, the LDA-BZW predictions of 5.017 Å and 0.65 eV for the equilibrium lattice constant and the band gap of c-InN have recently been corroborated by Schörmann et al 9 who found 5.01Ϯ 0.01 Å and 0.61 eV for these quantities, respectively. As summarized elsewhere, 7 the density fuctional theory ͑DFT͒-BZW calculations are totally ab initio and selfconsistent.…”
supporting
confidence: 72%
“…The LDA-BZW results that also agree well with experiment are shown in Table I. In particular, the LDA-BZW predictions of 5.017 Å and 0.65 eV for the equilibrium lattice constant and the band gap of c-InN have recently been corroborated by Schörmann et al 9 who found 5.01Ϯ 0.01 Å and 0.61 eV for these quantities, respectively. As summarized elsewhere, 7 the density fuctional theory ͑DFT͒-BZW calculations are totally ab initio and selfconsistent.…”
supporting
confidence: 72%
“…(zinc blende) or 0.71 eV (wurtzite) in extremely good agreement with measured values [53,57,[68][69][70][71]. In general, the improvement results from the good performance of the HSE03 starting point for materials that comprise d-electrons such as GaAs, CdS, GaN, ZnO, and ZnS, for which the mean absolute relative error of the HSE03 + 0 0 G W gaps is calculated to be 7.9%, while it is about 12.2% in the GGA + 0 0 G W approach.…”
Section: Quasiparticle Shiftssupporting
confidence: 72%
“…The HSE03 + 0 0 G W gaps approach recent measured values of 0.70 ± 0.05 eV for wurtzite [81] and 0.6 eV for zinc-blende [53,82] InN. The CBM at Γ is much lower in energy than the conduction-band edges at other points in k-space.…”
Section: γ (T ) γ (A )supporting
confidence: 51%
See 1 more Smart Citation
“…The ͑001͒ zinc-blende sample was grown on an ͑001͒ 3C-SiC substrate incorporating a zinc-blende GaN buffer layer, resulting in an estimated 95% zinc-blende phase InN. 9 Details of the various growth methods are reported elsewhere. [9][10][11][12] The x-ray photoemission spectroscopy ͑XPS͒ measurements were performed at room temperature using a Scienta ESCA300 spectrometer at the National Centre for Electron Spectroscopy and Surface Analysis, Daresbury Laboratory, UK.…”
mentioning
confidence: 99%